RELIGIUSITAS DAN INTELEKTUALITAS DALAM RUANG PUBLIK UNTUK MENGGIATKAN MODERASI BERAGAMA - Gomgom Purba; Andre Djaafar; Eko Agus Setiawan (JURNAL IMPARTA, 2023)
Indonesia as a multicultural and multiethnic nation, this is a privilege as well as a challenge to maintain diversity. The formation of public space allows various communities to grow and develop according to the capabilities of each step. With a high level of diversity, the Indonesian nation is a religion-centric society: seeing all things from a religious perspective. The interaction of religiosity and intellectuality in the public space can radiate values ​​and norms resulting from existing religions and cultures to ensure a sustainable shared life in a pluralistic society that can fulfill the same function and is eager to contribute to religious moderation. The method to be used is a literature review to survey the thoughts of figures and the scientific community who have an interest in discussing religiosity, intellectuality and religious moderation within the scope of Bhinneka Tunggal Ika. Religiosity implements the vision of diversity, in which religion appears as social capital to build a better life together. Religiosity pursues common ground in religious moderation, that is, there are universal teachings and values ​​that bring religions together. Intellectuality in a public space that is familiar but critical of conditions of intolerance to diversity will be able to save diversity from the rifts of religious communication and offer how a substantially better world can be created.